1986
DOI: 10.1002/cd.23219863206
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational influences on the development of early prodigious behavior: A case study approach

Abstract: In seeking early influences on the development of competence, researchers have typically been limited to one or two generations. Based on evidence from a case study of early prodigious achievement, it appears that "transgenerational" influences over several generations may also be at work. Such influences are not genetic and may be conscious or unconscious. Transgenerational Influences on the Development of Early Prodigious Behavior: A Case Study Approach David Henry Feldman, Lynn T. GoldsmithAlthough developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…3 Support for the consideration of psychological characteristics in TID comes from research that has indicated that performers who initially exhibited desirable physical and technical characteristics often failed to succeed unless they received encouragement, nurturance, training, and education. 48…”
Section: Introductionmentioning
confidence: 99%
“…3 Support for the consideration of psychological characteristics in TID comes from research that has indicated that performers who initially exhibited desirable physical and technical characteristics often failed to succeed unless they received encouragement, nurturance, training, and education. 48…”
Section: Introductionmentioning
confidence: 99%
“…It has been acknowledged that the acquisition of musical expertise throughout these phases requires considerable long-term investment of time and several studies have contributed to our knowledge of how best to support young musicians in sustaining their musical interest and motivation (Sosniak, 2006). In particular, the crucial role of parental support has been welldocumented (Creech, in press, Csikszentmihalyi et al, 1993), as has the influence of extended family (Feldman and Goldsmith, 1996), instrumental or vocal teachers (Creech and Hallam, 2003) , peer groups (Feldhusen, 1986) and role models (Sosniak, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…They could also play a significant role when it comes to the type of parents their own children will be in the future (Feldman & Goldsmith, 1986;Van Ijzendoorn, 1992). Intergenerational transmission of parenting can be defined as the transmission of parenting styles from generation to generation.…”
Section: Introductionmentioning
confidence: 99%